2023
DOI: 10.1186/s40359-023-01442-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between personality traits and smoking cessation among Chinese adults

Weiyun Jin,
Bensong Xian,
Longlong Zhao
et al.

Abstract: Background Although the tobacco epidemic is one of the greatest public health threats, the smoking cessation rate among Chinese adults is considerably lower. Personality information may indicate which treatments or interventions are more likely to be effective. China is the largest producer and consumer of tobacco worldwide. However, little is known about the association between smoking cessation and personality traits in China. Aim This study aime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…While a previous study examined the relationship between the Big Five personality traits of practitioners and the rates of smoking cessation of their patients [ 34 ], a relative paucity of studies addressed the use of personality-based interventions aimed at reducing tobacco use. For example, Jin et al [ 35 ] found that among Chinese men, reduced Neuroticism, decreased Extraversion, and increased Openness to Experience were linked with higher rates of quitting smoking. Additionally, lower Conscientiousness was associated with successful smoking cessation among Chinese women.…”
Section: Discussionmentioning
confidence: 99%
“…While a previous study examined the relationship between the Big Five personality traits of practitioners and the rates of smoking cessation of their patients [ 34 ], a relative paucity of studies addressed the use of personality-based interventions aimed at reducing tobacco use. For example, Jin et al [ 35 ] found that among Chinese men, reduced Neuroticism, decreased Extraversion, and increased Openness to Experience were linked with higher rates of quitting smoking. Additionally, lower Conscientiousness was associated with successful smoking cessation among Chinese women.…”
Section: Discussionmentioning
confidence: 99%